The complexity of olfactory art the use of scent as concept and context in the work of art - De Cupere, Peter (Amfiteater (Ljubljana), 2021)
The sense of smell is a powerful sense that offers many possibilities. To speak of olfactory art, there must be the intention to use odour or olfaction as both context and concept of the work of art. For this, we speak about the terms Olfactory Context and Olfactory Concept. The Olfactory Context can be divided into the Intrinsic and Intentional Odour Values. The intrinsic odour value brings with it their significance, while the intentional odour value gives an extra meaning to a smell. In addition, the Olfactory Perception is part of the Olfactory Concept of the artwork. To perceive this, the smell must be transferred to the spectator. The way in which an odour is transferred in a work largely determines how the smell is interpreted in relation to the work. The odour transfer and odour situation determine how an odour gets to the viewer. We call these methods of odour transfer Olfactory Transfers and divide them into five categories: Flowers, Smell Devices, Scent Spaces, Time and Translations. In most cases, Olfactory Transfers are used in crossovers. Together with the various possibilities of using the Olfactory Context, they also demonstrate the Complexity of Olfactory Art. The 1st Olfactory Art Manifest explains the differences in olfactory art.
Keywords: odour values; offactory transfers; Olfactory art manifest; olfactory concept; olfactory context; olfactory perception; olfaktorni umetniški manifest; prenos vonja; vonjalni koncept; vonjalni kontekst; vonjalno zaznavanje; vrednosti vonja